Mental imagery for addressing mechanisms underlying motor impairments in children with attention deficit hyperactivity disorder (ADHD) - Ron Baum, Arava; Franklin, Eric; Leitner, Yael; Abraham, Amit (Frontiers in Neurology, 2024)
Children with attention deficit hyperactivity disorder (ADHD) exhibit various degrees of motor and cognitive impairments in fine and gross motor skills. These impairments impact social functioning, while also hindering academic achievement, self-esteem, and participation. Specifically, motor impairments are not fully addressed by current therapies. For example, approximately 50% of children with ADHD exhibit significant motor impairments, as per clinical measures, while the other 50% experience more impairments in motor planning, execution and control than do typically developed (TD) children. Such findings indicate that ADHD-specific mechanisms may be underpinning motor impairments. In this paper, we outline ADHD impairments in motor planning, execution, and control, and the potential role of two such mechanisms: internal motor representation and timing perception. Next, we suggest mental imagery as an approach for treating ADHD motor impairments, potentially through addressing internal motor representation and timing perception.